Penerapan Digital Marketing Sebagai Strategi Pemasaran Ukm Rempeyek Nok Uus Dengan Video Cinematic Didukung Motion Grafis - Rahmat Gunawan; Rini Malfiany; Hamdan Yosep Pane (STEKOM PRESS, 2021)
Designing story scenarios for the Rempeyek Nok Uus UKM profile video, Making videos by recording, editing, and adding effects, Implementing marketing strategies with digital marketing techniques on social media. To obtain the necessary data, the things that must be done are interviews, observations, and documentation. So that they can get a mature concept for video production, the reference is from the information obtained during observations and interviews. Rempeyek Nok Uus has become a typical souvenir from Karawang and snacks or snacks from the Karawang area. Optimizing the digital platform as a place to order products so that it is easy for people to order, Active in social media, especially Instagram and Facebook in advertising products, Invite Instagram celebrities to work together who already have more than 10 K followers to promote products to customers.